(untitled) (Global Journal of Human-Social Science, 2021)
This research will propose the appreciation of local knowledge that came from intellectuals of tradition living at the Pradoso’s district located in Vitória da Conquista-BA city, and it aims to understand an epistemology that expresses their specific aspects. It will point out the knowledge using an ecology that will take into an account at the same time the nonscientific understanding from these people and a theoretical standing against the epistemological practices from the dominant paradigm of modernity. The data were collected using narratives with older people in Pradoso’s district as an empirical study of narrative inquiry about ways of life and environmental issues belonging to the culture of this peasant community. Hence, we believe the narratives offered a vital dialogue between emerged knowledge and scientific culture whose objective is describing the environmental issues at this community, valorizing traditional understanding and finding accordance with academic and scientific culture.